Sleep deprivation impairs neurovascular coupling and cerebral vasomotor reactivity - Krisztina Szonja Rab-Bábel; Dóra Sulina; Cecilia Daniel; Tibor Rab; Norbert Kozák; László Oláh (Scientific Reports)
Abstract Sleep deficiency increases the risk of cerebrovascular diseases. However, the effects of sleep deprivation (SD) on cerebral blood flow have been poorly studied. We examined the effect of 24-h of SD on the resting posterior cerebral artery (PCA) and middle cerebral artery (MCA) flow velocities (FV), the visually evoked FV response in the PCA (neurovascular coupling), and the hypercapnia-induced FV response in the MCA (cerebral vasoreactivity). Visual evoked potential (VEP) and transcranial Doppler examinations were performed in 25 healthy adults before and after 24-h of SD. Cerebral vasoreactivity was measured by breath-holding test in left and right MCA. The visually evoked FV response was evaluated in left and right PCA. There was a tendency for increased resting mean FV in PCA (p = 0.08) and MCA (p = 0.07) after SD. Both the visually evoked FV response in the PCA and the hypercapnia-induced FV increase in the MCA were significantly lower after than before SD, however, no change in VEP amplitudes was found. Our study suggested that the impaired functional stimulation-evoked FV response after SD was not due to a reduced neuronal activation, but probably to a decreased vasodilatory response. Negative effects of SD on cerebral hemodynamics were also demonstrated by reduced cerebral vasoreactivity.